1976
DOI: 10.1111/j.1476-5381.1976.tb07445.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Diethylcarbamazine Citrate

Abstract: I The cardiovascular effects of the anthelmintic drug diethylcarbamazine citrate (DECC) were examined in cats anaesthetized with pentobarbitone. There were two quite distinct haemodynamic responses, an initial transient hypotension (occurring within 10 s of an intravenous injection) and a pronounced secondary hypertension which reached a peak 30-60 s after the injection. 2 Within 10 s of an intravenous injection of DECC (2.5 to 10 mg/kg) there was hypotension, bradycardia and there were reductions in left vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…In contrast, increasing the dose of D4975 resulted in further elevations in arterial blood pressure. These, together with the changes in heart rate, are summarised in Table 1 One of the problems with using LV dP/dt..10, as an index of myocardial contractility is its partial dependence upon changes in preload and afterload, although the effect of the latter has been disputed (Schaper, Lewi & Jageneau, 1965 (Mason, 1969;Abaitey & Parratt, 1976). This involves recording left ventricular pressure (and dP/dt) using very fast paper speeds (in this case 1000 mm/s) and plotting isovolumic pressure against dP/dt at 10 mmHg intervals.…”
Section: Reultsmentioning
confidence: 99%
“…In contrast, increasing the dose of D4975 resulted in further elevations in arterial blood pressure. These, together with the changes in heart rate, are summarised in Table 1 One of the problems with using LV dP/dt..10, as an index of myocardial contractility is its partial dependence upon changes in preload and afterload, although the effect of the latter has been disputed (Schaper, Lewi & Jageneau, 1965 (Mason, 1969;Abaitey & Parratt, 1976). This involves recording left ventricular pressure (and dP/dt) using very fast paper speeds (in this case 1000 mm/s) and plotting isovolumic pressure against dP/dt at 10 mmHg intervals.…”
Section: Reultsmentioning
confidence: 99%
“…Pig coronary artery strips. In view of the increases in local myocardial blood flow observed when DECc was administered to anaesthetized cats (Abaitey & Parratt, 1976), experiments were made to see whether the drug relaxed isolated coronary arteries in vitro.…”
Section: Rat Portal Veinmentioning
confidence: 99%
“…It is also the drug of choice in destroying the microfilariae of Onchocerca volvulus in man. More recently, the drug has been used, with varying results, in the treatment of bronchial asthma (Mallen).In a recent study of the cardiovascular effects of DECC in anaesthetized cats (Abaitey & Parratt, 1976) we concluded that the drug has marked effects on sympathetic ganglia. The present study was designed to examine the effects of DECC on a variety of isolated smooth muscle preparations, including some which contain parasympathetic ganglia.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…DECC has been used in the treatment of filarial infections. It has been demonstrated that intravenous DECC administration into anaesthetized cats induces hypotension, bradycardia and a reduction in +dP/dt max (the maximum rate of increase in the left ventricular pressure) followed by hypertension and an increase in +dP/dt max and the myocardial blood flow (2). It is possible that DECC affects cardiovascular functions, but little is known about its mechanisms of action during these cardiac effects.…”
mentioning
confidence: 99%